Salivary steroid hormone response in trained men to running and circuit training sessions. Issue 15 (10th November 2011) - Tanner, A; Nielsen, B; Tetteh, J; Allgrove, J
Abstract : Cortisol (C) and testosterone (T) are important biomarkers of acute and chronic stress (Urhausen et al . Sports Med 1995;20 :251–76). However, it is unclear how different forms of training affect the response of these hormones. The purpose of this study was to examine the effect of various training sessions on salivary C and T in competitive male runners. Four trials were completed: (a) 30 min tempo run at lactate threshold (TEMP); (b) 30 min running alternating 3.5 min at 90% and 2 min at 30% VO2 max (INT); (c) 30 min circuit training with 3×10 exercises of 30 s with 30 s recovery between exercises (CIR) and d) 30 min rest (REST). Saliva samples were collected pre exercise and at 0, 15, 30 and 60 min post exercise and rating of perceived exertion (RPE) and heart rate (HR) were recorded. All samples were analysed with ELISA and salivary C was also measured with mass spectrometry. Preliminary data shows mean HR was: 161 ± 7, 159 ± 14, 130 ± 12 and 63 ± 1 beats per min for TEMP, INT, CIR and REST respectively with INT and TEMP higher than REST. RPE was: 15 ± 1, 16 ±2 and 13 ±1 for TEMP, INT and CIR respectively, INT was higher than CIR and TEMP. There was a difference in salivary C between the trials (p=0.038) and between time points (p=0.019). Area under curve (AUC) analysis indicated salivary C was higher than REST in INT (P=0.043) and TEMP (0.043) with INT showing the highest response (p=0.046). Salivary T showed an overall effect of time (p=0.024) with post exercise T higher than pre exercise (p=0.020). INT also showed a higher T response than REST (p=0.003) and TEMP tended to be higher (p=0.054). Salivary Peak HR correlated with peak salivary T for INT (r=0.961). This study implies an INT session increased salivary C and T more than TEMP and CIR despite no differences in mean HR, also peak HR may be linked to salivary T production which could be a useful to assess training stress.